HASIL BELAJAR SISWA DITINJAU DARI SELF-CONFIDENCE MATEMATIKA KELAS VIII SMP - Bella Jelsela; Hamdani Hamdani; Munaldus Munaldus (Jurnal AlphaEuclidEdu, 2022)
The purpose of this study was to determine the mathematics learning outcomes of class VIII students of SMP Negeri 01 Lumar in terms of Self-Confidence. The research subjects came from 20 students of class VIII A of SMP Negeri 01 Lumar in the 2021/2022 academic year who were selected by taking into account the considerations of the teacher in the field of mathematics studies. The research method used in this study is a qualitative descriptive research method, in the form of a case study. Collecting data in this study using a Self-Confidence Questionnaire, written test and interview guide. The results of the student self-confidence questionnaire showed that 11 students were in the high category, 5 students were in the medium category, and 4 students were in the low category. Student learning outcomes in the number pattern material are high. There are 15 students in the high category, 3 students in the medium category and 2 students in the low category. It can be seen from the percentage of student learning outcomes that fall into the high category above the average, which is 81.56%.